SPECIES STATUS OF A RICE YELLOW STEM BORER, SCIRPOPHAGA INCERTULAS (LEPIDOPTERA: PYRALIDAE) BASED ON CO I GENE SEQUENCES - Hari Sutrisno (BRIN Publishing (Penerbit BRIN), 2008)
Study on species status of a rice yellow stem borer, Scirpophaga incertulas(Lepidoptera: Pyralidae) was conducted. The objectives of the study were to explorethe genetic variation among populations of S. incertulas in Java and to clarify itsspecies status based on CO I gene sequences. The results showed that from the entire680-bp region of sequences from10 population in Java, 99 % were constant. The averageof estimated sequence divergences in the comparisons among populations withinS.incertulas was very low about 0.01%. The base composition was slightly A+T biased(C:0.15) with G+C contents was 37.09%. The result of phylogenetic analysis showedthat S.incertulas is a single species with S.innotata as its sister group. The differenceson the body-size, black spot at female’s forewing, forewing length within S.incertulasare solely natural variation.